2022
DOI: 10.3389/fphot.2021.825610
|View full text |Cite
|
Sign up to set email alerts
|

Speckle Noise Suppression Algorithm of Holographic Display Based on Spatial Light Modulator

Abstract: Holography has emerged as one of the most attractive three-dimensional display technologies. With the technological development of computer science and coherent light source, the computer-generated holography has been applied in many fields. However, the speckle noise of the holographic reconstructed image seriously affects the viewing experience. In this paper, the cause of speckle noise generation in holographic display is introduced. Then, discussions about the speckle noise suppression methods are provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Numerical reconstruction is performed to verify the validity of our method. The reconstructed image quality by the proposed method is similar to that by SGD in terms of peak-signal-noise-ratio (PSNR) and similarity index measure (SSIM) [12], while the reconstructed images show less speckle noise than SGD due to the smooth phase distribution in the reconstructed plane [13]. Moreover, the proposed method can infer a hologram about 100 times faster than SGD (about 13s for SGD and 0.13s for proposed method respectively)…”
Section: Objective and Backgroundmentioning
confidence: 74%
“…Numerical reconstruction is performed to verify the validity of our method. The reconstructed image quality by the proposed method is similar to that by SGD in terms of peak-signal-noise-ratio (PSNR) and similarity index measure (SSIM) [12], while the reconstructed images show less speckle noise than SGD due to the smooth phase distribution in the reconstructed plane [13]. Moreover, the proposed method can infer a hologram about 100 times faster than SGD (about 13s for SGD and 0.13s for proposed method respectively)…”
Section: Objective and Backgroundmentioning
confidence: 74%
“…Therefore, SAR exhibits excellent penetration capability and can acquire high-quality remote sensing data in adverse weather conditions such as clouds, haze, rain, or snow, making it an all-weather remote sensing technology [2][3][4][5][6]. However, in the process of SAR imaging, the generation of speckle noise is inevitable [7], which significantly affects the quality and resolution of SAR images [8]. To overcome this issue, there are currently two main strategies:…”
Section: Introductionmentioning
confidence: 99%
“…Several related studies predominantly focus on technical noise, such as photon noise and quantization noise, and coherent noise, such as speckle noise [12][13][14]. The authors in [8] have shown that deep neural networks are susceptible to white Gaussian noise.…”
mentioning
confidence: 99%